PEMAKNAAN PUISI â€œKEBUN HUJANâ€ DAN â€œIBU HUJANâ€ DALAM KUMPULAN PUISI SELAMAT MENUNAIKAN IBADAH PUISI KARYA JOKO PINURBO DENGAN KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE - Sugiarti Sugiarti; Widowati Widowati (CARAKA, 2019)
This study aims to describe the unit of a sign as follows. 1) Icons, indices and symbols in the poem "Rain Gardens". 2) Icons, indices and symbols in the poem "Rainy Mother". 3) The meanings contained in the poems "Rain Gardens" and "Mother Rain" in a collection of poems Congratulations on Performing Poetry Worship by Joko Pinurbo. This research is a type of qualitative research. The data used is a sign in the form of words, phrases, sentences, lines, and stanzas in the poems "Rain Gardens" and "Mother Rain". The data sources used in this study are the poems "Rain Gardens" and "Mother Rain" which are collected in a collection of poems, Congratulations on Poetry Worship by Joko Pinurbo. The research instrument in this study is the researchers themselves who are armed with a set of concepts about signs and meanings. The data collection technique used in this study is to read the note. The data analysis technique used in this study is a qualitative descriptive analysis method. The results of the analysis of the poetry "Rain Gardens" and "Mother of Rain" as follows. 1) Icons, indices, and symbols in the poem "Rain Gardens" are found: (a) icons (in pieces / children of rain / which are interpreted as rain / drizzle), (b) index (in word fragments / fall / interpreted by the process of falling rain), (c) symbols (in fragments / sun / interpreted with hope and new enthusiasm). 2) Icons, indices, and symbols on the poem "Rainy Mother" by finding: (a) icons (in pieces / three kilograms of rain / weighted by human burdens in living life), (b) indexes (on pieces / shivering alone / interpreted as a condition of loneliness, (c) symbol (in fragments / rain / interpreted by the arrival of gifts and calamities) 3) Meaning in the poem "Rain Gardens" and "Mother of Rain" as follows. (a) Poetry "Rain Gardens" has the meaning of the phenomenon of natural disasters that make the despair of the victim, (b) Poetry "Mother of Rain" has the meaning of the journey of human life as an example of achieving the perfection of life.